Insights into Glycogen Metabolism in Chemolithoautotrophic Bacteria from Distinctive Kinetic and Regulatory Properties of ADP-Glucose Pyrophosphorylase from Nitrosomonas europaea - Machtey, Matías (2012)
Nitrosomonas europaea is a chemolithoautotroph that obtains energy by oxidizing ammonia in the presence of oxygen and fixes CO2 via the Benson-Calvin cycle. Despite its environmental and evolutionary importance, very little is known about the regulation and metabolism of glycogen, a source of carbon and energy storage. Here, we cloned and heterologously expressed the genes coding for two major putative enzymes of the glycogen synthetic pathway in N. europaea, ADP-glucose pyrophosphorylase and glycogen synthase. In other bacteria, ADP-glucose pyrophosphorylase catalyzes the regulatory step of the synthetic pathway and glycogen synthase elongates the polymer. In starch synthesis in plants, homologous enzymes play similar roles. We purified to homogeneity the recombinant ADP-glucose pyrophosphorylase from N. europaea and characterized its kinetic, regulatory, and oligomeric properties. The enzyme was allosterically activated by pyruvate, oxaloacetate, and phosphoenolpyruvate and inhibited by AMP. It had a broad thermal and pH stability and used different divalent metal ions as cofactors. Depending on the cofactor, the enzyme was able to accept different nucleotides and sugar phosphates as alternative substrates. However, characterization of the recombinant glycogen synthase showed that only ADP-Glc elongates the polysaccharide, indicating that ATP and glucose-1-phosphate are the physiological substrates of the ADP-glucose pyrophosphorylase. The distinctive properties with respect to selectivity for substrates and activators of the ADP-glucose pyrophosphorylase were in good agreement with the metabolic routes operating in N. europaea, indicating an evolutionary adaptation. These unique properties place the enzyme in a category of its own within the family, highlighting the unique regulation in these organisms.